Accelerators simulation of structure-phase evolution and radiation resistance of materials for nuclear reactors - Neklyudov, I.; Voyevodin, V.; Zelenskiy, V. (Вопросы атомной науки и техники, 2009)
At this presentation activity of KIPT which during many years was involved into the field of
simulation and investigation of Radiation Damage in reactor materials, is described. Well known
that charge particle accelerators are widely used for the purpose of obtaining express information
on radiation resistance and investigating physical nature of the radiation. During irradiation with
charged particle beams one could reproduce and examine under well-controlled conditions
practically all the known radiation effects and investigate physical nature of these effects in more
detail. Simulation experiments together with results of reactor investigation much contribute to
radiation physics phenomena, radiation and ion-beam technologies as well as solving problems
of creation low-activated materials with good radiation resistance. Modern status of simulation
experiments in investigation of structure-phase transformations in reactor materials during
irradiation is discussed. В представленій роботі описано діяльність ХФТІ протягом багатьох років в галузі
імітації та дослідженні радіаційного пошкодження реакторних матеріалів. Добре відомо,
що прискорювачі заряджених часток широко використовуються з метою отримання
експрес-інформації щодо радіаційної стійкості і для вивчення фізичної природи
випромінювання. У процесі опромінення пучком заряджених часток можна відтворити та
дослідити в добре контрольованих умовах практично всі відомі радіаційні ефекти, а також
дослідити фізичну природу цих ефектів більш докладно. Імітаційні експерименти нарівні з
реакторними випробуваннями вносять вагомий вклад в явища радіаційної фізики,
радіаційні та іонні технології, а також в рішення проблем слабкоактивуємих матеріалів з
високою радіаційною стійкістю. Обговорюється сучасний статус імітаційних
експериментів в дослідженні структурно-фазових перетворень в реакторних матеріалах
під опроміненням. В предлагаемой работе приводится описание деятельности ХФТИ на протяжении
многих лет в области имитации и исследования радиационного повреждения реакторных
материалов. Хорошо известно, что ускорители заряженных частиц широко применяются с
целью получения экспресс-информации о радиационной стойкости и для исследования
физической природы излучения. В процессе облучения пучком заряженных частиц можно
воспроизвести и исследовать в хорошо контролируемых условиях практически все
известные радиационные эффекты, а также исследовать физическую природу этих
эффектов более подробно. Имитационные эксперименты наряду с реакторными
испытаниями вносят весомый вклад в явления радиационной физики, радиационные и
ионные технологии, а также в решение проблем создания слабоактивируемых материалов
с высокой радиационной стойкостью. Обсуждается современный статус имитационных
экспериментов в исследовании структурно-фазовых превращений в реакторных
материалах под облучением.